2018
DOI: 10.1007/s10142-018-0628-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of grapevine under salinity and identification of key genes responsible for salt tolerance

Abstract: The negative effects of soil salinity towards grape yield depend upon salt concentration, cultivar type, developmental stage, and rootstock. Thompson Seedless variety of grape plant is considered moderately sensitive to salinity when grown upon its own root stock. In recent epoch, identification of key genes responsive to salinity offers hope to generate salinity-tolerant crop plants by their overexpression through genetic manipulation. In the present report, salt responsive transcriptome analysis of Thompson … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 54 publications
0
22
1
Order By: Relevance
“…For the purpose of this analysis we assumed that VvLidh (VIT_16s0100g00290) represents transcripts of both VvLidh1 and VvLidh3. Most datasets ( Table 1) exhibited no changes in expression of VvLidh nor Vv2kgr (VIT_09s0002g04300), including experiments featuring water limitation (Berdeja et al, 2015;Catacchio et al, 2019), cold night temperature (Sawicki et al, 2019), elevated light (du Plessis et al, 2017), diurnal regulation (Rienth et al, 2014), salt stress in leaves (Upadhyay et al, 2018;Das and Majumder, 2019), increased source-sink ratio via cluster thinning (Pastore et al, 2011), copper stress (Leng et al, 2015) and abscisic acid application (Rattanakon et al, 2016;Pilati et al, 2017). In an experiment reporting the differential terroir effect on Cabernet Sauvignon berries in Bordeaux and Reno, there was also no change, but these experimental samples were skins collected during late ripening so expression of VvLidh was likely low anyway (Cramer et al, 2020).…”
Section: Stress Tolerancementioning
confidence: 99%
“…For the purpose of this analysis we assumed that VvLidh (VIT_16s0100g00290) represents transcripts of both VvLidh1 and VvLidh3. Most datasets ( Table 1) exhibited no changes in expression of VvLidh nor Vv2kgr (VIT_09s0002g04300), including experiments featuring water limitation (Berdeja et al, 2015;Catacchio et al, 2019), cold night temperature (Sawicki et al, 2019), elevated light (du Plessis et al, 2017), diurnal regulation (Rienth et al, 2014), salt stress in leaves (Upadhyay et al, 2018;Das and Majumder, 2019), increased source-sink ratio via cluster thinning (Pastore et al, 2011), copper stress (Leng et al, 2015) and abscisic acid application (Rattanakon et al, 2016;Pilati et al, 2017). In an experiment reporting the differential terroir effect on Cabernet Sauvignon berries in Bordeaux and Reno, there was also no change, but these experimental samples were skins collected during late ripening so expression of VvLidh was likely low anyway (Cramer et al, 2020).…”
Section: Stress Tolerancementioning
confidence: 99%
“…As previous studies have shown, a systematic and organismal response occurs when plants suffer one or more bio/abiotic stress, mediated by Ca 2+ , ROS, phytohormones, and cellular, genetic or metabolic processing 44,45 . We only investigated the correlation of five co-upregulated genes with other well-identified resistance genes; however, the complexity of the regulatory networks was greater than expected (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This gave a hint of the magnitude of the interspecific variation within the Vitis genus (Wan et al 2013), which may play a role in differences between rootstock species and V. vinifera when it comes to stress tolerance. Nevertheless, the grapevine reference genome has been used to map differentially expressed genes under salinity found not only in V. vinifera cultivars (Guan et al 2018, Upadhyay et al 2018, Das and Majumder 2019, but also in other species from the same genus that are used as rootstocks (Henderson et al 2014) leaving possible key gaps from rootstock genomic regions that do not match with the V. vinifera reference genome, and consequently genes involved in salt tolerance that are as yet unknown.…”
Section: Present and Future Perspectivesmentioning
confidence: 99%
“…have been suggested by transcriptomic studies (e.g. Henderson et al 2014, Guan et al 2018, Upadhyay et al 2018, Das and Majumder 2019) and serve as a guide to determine which mechanisms should receive functional characterisation via heterologous systems or through gene manipulation in grapevine. Genetic manipulation techniques would aid towards understanding grapevine gene function; however, the production of grapevine transgenic plants is slow and laborious at present (Vidal et al 2010), thus functional studies of grapevine genes, often involves cloning them into other species, such as tobacco ( Nicotiana spp.)…”
Section: Present and Future Perspectivesmentioning
confidence: 99%